What Has Man Made of Man? An Examination of the Epic Self - Saputra, Buyung Ade; Sari, Hanifah Yulia; Indriyani, Vivi (Lingua Susastra, 2025)
This research examines the concept of the Epic Self in William Wordsworth's poem "Lines Written in Early Spring." The Epic concept predates the Romantic Era, but its meaning has evolved. While epic literature focuses on famous figures, the Romantic Era centres the author as the hero. This study utilizes the dialectical method, involving thorough readings of the poem and related sources. The analysis examines each stanza and line, linking them to illustrate the Epic Self. The dialectical method is suitable as it reveals the Epic Self by connecting the poem's content to the author's history. The research finds that the Epic Self emerges as a rejection of Reason's dogmas, prioritizing human emotions and freedom in daily life. An example is the line, "And 'tis my faith that every flower / Enjoys the air it breathes," suggesting that happiness can arise from any moment. This research aims to provide a foundation for understanding the Epic Self, offering an alternative perspective on non-popular works like "Lines Written in Early Spring."